An FRET-ICT-based ratiometric fluorescent and colorimetric probe for pH monitoring in lysosomes and water. (September 2021) - Li, Zhang-Yi; Cui, Xiao-Ling; Xiao, Meng-Min; Miao, Jun-Ying; Zhao, Bao-Xiang; Lin, Zhao-Min
Abstract: A novel FRET-ICT-based ratiometric fluorescent and colorimetric pH probe (BDMNP ) was developed. BDMNP exhibited 96% energy transfer efficiency and good linear response in the pH ranges of 5.4–6.8 (pKa  = 6.10) with high selectivity and sensitivity. BDMNP has been successfully applied to monitor lysosomal pH changes in living cells. Meanwhile, BDMNP can also be used to detect the subtle pH changes of a variety of environmental water samples. Graphical abstract: Image 1 Highlights: A novel FRET-ICT-based pH probe BDMNP was designed to detect pH value. BDMNP has a large Stokes shift of 197 nm, and 96% energy transfer efficiency. BDMNP achieved the dual colorimetric and ratiometric fluorescent strategy. BDMNP achieved detection of lysosomal pH changes. BDMNP can linearly detect weak acidic pH in environmental water samples.